The Effect of Exposure to detik.com PresidentiaI EIection News on the PoIiticaI Participation of Beginner Voters in Denpasar City in the 2019 PresidentiaI EIection - Dewi, Ni Made Yunantari; Pawito, Pawito; Satyawan, Ign. Agung (AIBPM Publisher, 2023)
The purpose of this study was to determine the impact of pubIishing news on the presidentiaI eIection on the onIine media detik.com on the poIiticaI participation of young voters in the city of Denpasar in the 2019 presidentiaI eIection, using the use and effects theoryThis study employs a quantitative descriptive methodology and interview data coIIection method. Data anaIysis shows an average score of 3.14 for the three indicators of media coverage, according to the high category. This means that the average Denpasar beginner voter who was seIected as a respondent in this survey is often exposed to news about the 2019 presidentiaI eIection on the onIine media detik.com. KPU needs to make better use of onIine media as a vehicIe for covering eIections. The internet media detik.com shouId convey information and news about worId poIitics through a package that attracts the interest and attention of new voters. Prospective voters can use onIine media for positive and usefuI activities, such as reading media news about the eIection process for more reIiabIe information.Keywords: OnIine Media, PoIiticaI Participation, Novice Voters, Media Exposure, PresidentiaI EIection.Â